Gut mycobiome and neuropsychiatric disorders: insights and therapeutic potential - Hadrich, Ines; Turki, Mariem; Chaari, Imen; Abdelmoula, Balkiss; Gargouri, Rahma; Khemakhem, Nahed; Elatoui, Dhawia; Abid, Fatma; Kammoun, Sonda; Rekik, Mona; Aloulou, Samir; Sehli, Mariem; et al. (Frontiers in Cellular Neuroscience, 2025)
BackgroundThe human gut mycobiome, a minor but integral component of the gut microbiome, has emerged as a significant player in host homeostasis and disease development. While bacteria have traditionally been the focus of gut microbiome studies, recent evidence suggests that fungal communities (mycobiota) may also play a crucial role in modulating health, particularly in neuropsychiatric disorders.ObjectiveThis review aims to provide a comprehensive overview of current knowledge on the relationship between the gut mycobiome and neuropsychiatric disorders, exploring the potential of targeting fungal communities as a novel therapeutic strategy.MethodsWe summarized recent findings from metagenomic analyses that characterize the diversity and composition of gut mycobiota and discuss how these communities interact with the host and other microorganisms via the gut-brain axis. Key methodologies for studying mycobiota, such as high-throughout sequencing and bioinformatics approaches, were also reviewed to highlight advances in the field.ResultsEmerging research links gut mycobiota dysbiosis to conditions such as schizophrenia, Alzheimer’s disease, autism spectrum disorders, bipolar disorder, and depression. Studies indicate that specific fungal populations, such as Candida and Saccharomyces, may influence neuroinflammation, gut permeability and immune responses, thereby affecting mental health outcomes.ConclusionUnderstanding the gut mycobiome’s role in neuropsychiatric disorders opens new avenues for therapeutic interventions, including antifungal treatments, probiotics, and dietary modifications. Future research should integrate multi-omics approaches to unravel the complex interkingdom interactions within the gut ecosystem, paving the way for personalized medicine in mental health care.